Mengurangi Degradasi Moral dan Penguatan Karakter Anak Melalui Peran Catur Guru di Tengah Pandemi Covid-19 - Putu Febri Sri Suandari; Ni Nengah Selasih (UHN I Gusti Bagus Sugriwa Denpasar, 2021)
Education is one of the most important things that is able to be a change in the world and in changing the younger generation to be better and have character. With the existence of an education that is complemented by religious teachings it self, it will streng then character and reduce the moral and ethical degradation or decline that occurs in every nation's future child. Cultivators of noble moral values, ethics and religious teachings must be planted from an early age so that children become accustomed to them and are able to understand behaviors that should be avoided and prohibited. Therefore the role of parents is very influential on the character of the child because the family is the primary or primary education that the child gets. In addition, to reduce the current moral degradation or deterioration that is prevalent in life, there is a need for cooperation between parents, educators and the government to be able to create a good young generation. Therefore, Catur guru has a very important role in reducing moral degradation and strengthening children's character. Guru Rupaka and Guru Pengajian as formal and non-formal education obtained by children, must synergize with each other in educating, shaping children's character and instilling ethical, moral, character and religious teachings in children from an early age. And supported by Guru Wisesa or the government in making regulations in the world of education.